Efficacy of aqueous and acetone phytoextracts against Ralstonia solanacearum causing bacterial wilt of tomato - S.S. WAGH and D.V. PAWAR, R.K. BANNIHATTI, A.P. SURYAWANSHI* (Indian Phytopathology, 2016)
Bacterial wilt caused by Ralstonia solanacearum is one of the devastating diseases of tomato (Lycopersicum esculentum) crop. The pathogen/disease, being soil borne is very difficult and uneconomical to manage alone with chemicals. Therefore, the present study was undertaken to assess bio-efficacy of 11 aqueous and acetone phytoextracts against R. solanacearum, applying inhibition zone assay technique. Results revealed that the test aqueous and acetone phytoextracts were bacteriostatic against the test bacterium which significantly inhibited its growth, over untreated control. However, significantly highest average zone of inhibition was recorded with acetone and aqueous extracts of A. sativum (19.10 and 18.40 mm, respectively), followed by A. cepa (17.38 and 15.23 mm, respectively), C. longa (15.90 and 14.33 mm, respectively), A. indica (15.00 and 13.40 mm, respectively), O. sanctum aqueous extract (12.87 mm) and acetone extract of L. innermis (13.46 mm).